The Ministry of Industry, Trade and Small and Medium Projects Decree No. 288 of the Year 2015 On Imposing Temporary Precautionary Measures On White Sugar Imports = وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 288 لسنة 2015 بفرض تدابير وقائية مؤقتة على الواردات من صنف السكر الأبيض - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic